Wear Study of Mg-SiCp Reinforcement Aluminium Metal Matrix Composite - M. A., Maleque; M. M., Rahman (Faculty Mechanical Engineering, UMP, 2016)
Lightweight aluminium metal matrix composite materials hold potential requisite for modern tribological applications due to its inherent and better wear resistant properties over monolithic metallic materials. This study emphasised on the development of Al based metal matrix composite with SiCp as a reinforcement and magnesium (Mg) as a wetting agent using hybrid stir casting process. The study further analysed the effects of different size variations of silicon carbide particles such as the coarse particle size, fine particle size, intermediate particle size and mixed particle size in the fabrication of the composites on the hardness and wear properties. The pin-on-disc test was also done at room temperature in a dry sliding wear condition. It was observed that the mixed particle size SiCp in composite exhibited superior hardness with the value of 98.2 compared to other particle sizes of SiCp. This is due to the fact that mixed particle size supports a greater fraction of applied load while the fine and intermediate particle sizes sustain the hardening due to dislocation. The multiple particle size reinforced composite exhibits better performance than the single particle size in terms of wear resistance as the wear rate was the lowest with the value of 0.99 X 10-5. It can be concluded that the Mg addition in the composite showed better and tailored properties with a mixed particle size of SiCp of aluminium metal matrix composite.